Results from the AAA Study - Vinall, Maria (MD Conference Express, 2009)
Results from the Aspirin for Asymptomatic Atherosclerosis [AAA] study showed no support for the routine use of aspirin for the primary prevention of vascular events in people with asymptomatic atherosclerosis.